Past and present work practices of European interventional cardiologists in the context of radiation protection of the eye lens—results of the EURALOC study. (12th June 2018) - Domienik-Andrzejewska, Joanna; Ciraj-Bjelac, Olivera; Askounis, Panagiotis; Covens, Peter; Dragusin, Octavian; Jacob, Sophie; Farah, Jad; Gianicolo, Emilio; Padovani, Renato; Teles, Pedro; Widmark, Anders; Struelens, Lara
Abstract: This paper investigates over five decades of work practices in interventional cardiology, with an emphasis on radiation protection. The analysis is based on data from more than 400 cardiologists from various European countries recruited for a EURALOC study and collected in the period from 2014 to 2016. Information on the types of procedures performed and their annual mean number, fluoroscopy time, access site choice, x-ray units and radiation protection means used was collected using an occupational questionnaire. Based on the specific European data, changes in each parameter have been analysed over decades, while country-specific data analysis has allowed us to determine the differences in local practices. In particular, based on the collected data, the typical workload of a European cardiologist working in a haemodynamic room and an electrophysiology room was specified for various types of procedures. The results showed that when working in a haemodynamic room, a transparent ceiling-suspended lead shield or lead glasses are necessary in order to remain below the recommended eye lens dose limit of 20 mSv. Moreover, the analysis revealed that new, more complex cardiac procedures such as chronic total occlusion, valvuloplasty and pulmonary vein isolation for atrial fibrillation ablation might contribute substantially to annual doses, although they are relatively rarely performed. The results revealed that considerable progress has been made in the use of radiation protection tools. While their use in electrophysiology procedures is not generic, the situation in haemodynamic procedures is rather encouraging, as ceiling-suspended shields are used in 90% of cases, while the combination of ceiling shield and lead glasses is noted in more than 40% of the procedures. However, we find that still 7% of haemodynamic procedures are performed without any radiation protection tools.